Chemometric analysis for the classification, pattern recognition and clustering of wines from the indigenous Cypriot cultivar 'Xynisteri' based on their vintage - Kokkinou, D.; Pavlou, A.; Mina, Minas; Manganaris, George A. (My University, 2023)
In this preliminary study, we have applied an array of spectrophotometric assays in combination with ATR-FTIR and chemometrics, to evaluate the impact of vintage on the phenolic content of Cypriot monovarietal wines produced from the predominant indigenous cultivar 'Xynisteri'. This indigenous cultivar, despite its economic impact is poorly characterized. Analysis took place over five growing seasons (2014-2019) and results indicated an enhanced phenolic acid content on wines of old vintages with both assays applied (Folin-Ciocalteu, Waterman and Mole's). The flavonoid content did not monitor a specific pattern on wines from different vintages, while the lowest content of flavon-3-ols was registered on wines of 2014, following a reverse pattern to the one monitored for total phenolic content. In order to determine the ability of the above assays to characterize the chemical profile of wines produced from 'Xynisteri' of varying vintage years, and to find out whether their chemical profile can be linked with explicit compositional properties, principal component analysis (PCA) was additionally performed. To what extent, the white cultivar 'Xynisteri' can be considered amenable to ageing need to be dissected with further analyses that will encompass also evaluation of sensorial properties. Results reported herein need to be further validated with an increased number of samples tested prior to be exploited by the winemakers and the viticulture team to amend protocols for better expression of the unique varietal character of 'Xynisteri' upon vinification.
Keywords: ATR-FTIR; chemometrics; indigenous cultivar; phenolic compounds; Vitis vinifera